Tackling disinformation in K-12 through in-service teacher training and journalists’training: preliminary results from the Iberifier Hub - Tomé, V.; Crespo, M. (Global Media Education Summit (2-4 March 2023), 2023)
This paper presents the preliminary results of four in-service teacher training courses on tackling disinformation in K-12 classrooms that were developed in Portugal between October 2022 and February 2023. The trainings were the first of a course series that will be implemented in Portugal and Spain until February 2024, following the production and validation of pedagogical manuals for trainers and learners. The trainings were led by trained journalists, certified as teacher trainers by the Portuguese Ministry of Education, during the project ‘Media Literacy and Journalism: pedagogic practices with and about media’ (2017 - …), focused on training teachers in media education. Since its arrival to the field, in partnership with the Portuguese Ministry of Education, more than 150 journalists and other media professionals have worked with 300 teachers, who have developed school projects with around 5000 preschool children and K-12 students. Firstly, journalists helped teachers design projects adapted to their schools and communities. After the training, they continued to offer teachers regular support and monitored the developments. Therefore, some of the projects extended beyond the training course and are still ongoing. The trainings specifically focused on tackling disinformation are being developed on behalf of the Iberian Digital Media and Fact-checking Hub (IBERIFIER), an observatory in Spain and Portugal, funded by the European Commission and linked to the European Digital Media Observatory (EDMO) and made up of twelve universities, five fact-checking organizations and news agencies, and six multidisciplinary research centers.